Experimental techniques for in-ring reaction experiments. (26th November 2015) - Mutterer, M; Egelhof, P; Eremin, V; Ilieva, S; Kalantar-Nayestanaki, N; Kiselev, O; Kollmus, H; Kröll, T; Kuilman, M; Chung, L X; Najafi, M A; Popp, U; et al.
Abstract: As a first step of the EXL project scheduled for the New Experimental Storage Ring at FAIR a precursor experiment (E105) was performed at the ESR at GSI. For this experiment, an innovative differential pumping concept, originally proposed for the EXL recoil detector ESPA, was successfully applied. The implementation and essential features of this novel technical concept will be discussed, as well as details on the detectors and the infrastructure around the internal gas-jet target. With 56 Ni(p, p) 56 Ni elastic scattering at 400 MeV u −1, a nuclear reaction experiment with stored radioactive beams was realized for the first time. Finally, perspectives for a next-generation EXL-type setup are briefly discussed.